Pengaruh Proporsi Tepung Kacang Kedelai (Glycine Max L. Merr) dan Tepung Beras (Oryza Sativa) terhadap Nilai Kalori, Kadar Protein dan Mutu Organoleptik Biskuit - Ermina Syainah; Fitria Rahmaningsih (HB PRESS, 2022)
Autism is a complex developmental disorder involving communication, social interaction and imaginary. The risk factors that can increase the progressiveness of this disorder are gluten and casein. The alternative solution is making gluten-free and casein-free (CFCF) biscuit using soybean and rice flour. This study aimed to know the effect of soybean and rice flour proportion to calorie, protein contents, and organoleptic characteristics of biscuit. This pre-experimental study used a completely randomized design to against 3 times to treatments and replications. It used one group treated with P0 = 100% wheat flour and oat as control; and others P1 = 60%: 40%, P2 = 70%: 30% and P3 = 80%: 20% with the ratio of soybean flour and rice flour. The average of protein content biscuit on the treatment of P0 (control), P1, P2, and P3 were 9,15%, 15,94%, 18,74%, and 19,45%, respectively. The average of calorie biscuit on the treatment groups were 4382,82 cal /g, 3914,45 cal /g, 3996,13 cal/g, and 4484,33 cal /g, respectively. The higher the proportion of soybean flour, the higher the calorie content in biscuits. The protein and calorie in the best treatment were 448,43 kcal to control 438,28 kcal and 19,45% to control 9,15%, respectively. The most preferred organoleptic was P3. The soybean flour and rice flour proportion did not influence the biscuit’s color and flavor, but it affected the odor and texture. There was difference between calorie and protein contents, and organoleptic quality in the best treatment biscuit to control.